A generic object-based support system for manufacturing processes. (20th February 2007) - Lau, H.C.W.; Tang, C.X.H.; Lee, C.K.M.; Ho, G.T.S.
In this paper, an Object-Based Support System (OBSS), which is designed to be deployed in existing manufacturing firms with the objective to reorganise the job and process functions concerned, is proposed. The implementation of this system is based on the object technology concept, which considers most of the enterprise applications to consist of reusable software components, which are themselves built by other elements made up of relevant manufacturing data. Whenever there is any change of requirements, only the reusable software components are altered or just slightly modified to form a new component. More importantly, the flexibility and responsiveness of companies are greatly enhanced with the support of a generic object-based system that is specifically designed for improving the manufacturing activities of individual enterprises. The infrastructure with the developed and tested prototype system for validating its 'reconfigurability' is covered in the paper.